Tip rates, phylogenies and diversification: What are we estimating, and how good are the estimates?. Issue 6 (11th February 2019) - Title, Pascal O.; Rabosky, Daniel L.
Abstract: Species‐specific diversification rates, or 'tip rates', can be computed quickly from phylogenies and are widely used to study diversification rate variation in relation to geography, ecology and phenotypes. These tip rates provide a number of theoretical and practical advantages, such as the relaxation of assumptions of rate homogeneity in trait‐dependent diversification studies. However, there is substantial confusion in the literature regarding whether these metrics estimate speciation or net diversification rates. Additionally, no study has yet compared the relative performance and accuracy of tip rate metrics across simulated diversification scenarios. We compared the statistical performance of three model‐free rate metrics (inverse terminal branch lengths; node density metric; DR statistic) and a model‐based approach (Bayesian analysis of macroevolutionary mixtures [BAMM]). We applied each method to a large set of simulated phylogenies that had been generated under different diversification processes. We summarized performance in relation to the type of rate variation, the magnitude of rate heterogeneity and rate regime size. We also compared the ability of the metrics to estimate both speciation and net diversification rates. We show decisively that model‐free tip rate metrics provide a better estimate of the rate of speciation than of net diversification. Error in net diversification rate estimates increases as a function of the relative extinction rate. In contrast, error in speciation rate estimates is low and relatively insensitive to extinction. Overall, and in particular when relative extinction was high, BAMM inferred the most accurate tip rates and exhibited lower error than non‐model‐based approaches. DR was highly correlated with true speciation rates but exhibited high error variance, and was the best metric for very small rate regimes. We found that, of the metrics tested, DR and BAMM are the most useful metrics for studying speciation rate dynamics and trait‐dependent diversification. Although BAMM was more accurate than DR overall, the two approaches have complementary strengths. Because tip rate metrics are more reliable estimators of speciation rate, we recommend that empirical studies using these metrics exercise caution when drawing biological interpretations in any situation where the distinction between speciation and net diversification is important.